INFLUENCE OF LOW OXYGEN CONDITION OF BONE MARROW MESENCHYMAL STEM CELL - setyowardoyo, nugroho (Journal of Stem Cell Research and Tissue Engineering, 2018)
The state of low oxygen levels known as hypoxia in humans is considered a dangerous condition is apparently a normal physiological condition and required by the stem cells as they are in the body. Mesencyimal Stem Cells (MSCs) require physiologically optimal conditions of low O2 tension of 1-3% in the bone marrow. The purpose of this study was to reveal the difference between in vitro culture of MSC in normoxia condition (20% O 2 concentration) with hypoxia condition (1% O2 content) especially in terms of viability, pluripotent properties, and MSC proliferation ability of the culture it produces. This research is an explorative laboratory research invitro on Bone Marrow Mesenchymal Stem Cells (BMSCs) culture using hypoxia condition. The study design used Randomized Control Group Post-Test Only Design. This research was conducted for 2 months. There was a significant difference in mean slow proliferation based on the number of Least-like CFU-Cs between the control group, treatment group 1 and treatment group 2, the mean percentage of the number of cells expressing the OCT4 coding gene on immunofluorosense examination between the control group, 1 and the treatment group 2 and the mean percentage of cell numbers expressing the OCT4 coding gene on the immunofluorosense examination between the control group, the treatment group 1 and the treatment group 2 showing p <0.01. There was a significant difference of percentage of non-absorbing color cell number of trypsin blue (viable cells) between control group, treatment group 1, and treatment group 2 showing p value <0.05. This suggests that the precondition of culture with normoxia provides an opportunity for cells to adapt and proliferate before being conditioned in hypoxic cultures. Cultures with hypoxic conditions and preconditions of normoxia are the best culture conditions because they produce cells that are capable of maintaining pluripotency properties while still having better proliferation and viability capability compared with direct hypoxia conditions.Keywords: Hypoxia, normoxia, bone marrow, mesenchymal stem cells.